Participatory Forest Resource Management: A Strategy Based on Local Knowledge At Forest Management Unit Kulawi - Darwis Darwis; Golar Golar; Naharuddin Naharuddin; Adam Malik; Imran Rachman; Hasriani Muis; Sudirman Daeng Massiri; Ramal Yusuf; Samsurizal M. Suleman (Postgraduate, University of Mataram, 2024)
Forests play a vital role in supporting the livelihoods of surrounding communities and have the potential to significantly boost local economies. However, this dependence can sometimes threaten the sustainability of forest ecosystems. To address this, sustainable management should be at the forefront of utilizing existing forest resources. A study focusing on community empowerment in managing forestry commodities is essential to optimize the sustainable use of natural resources in Central Sulawesi Province. This research aims to identify factors influencing community empowerment in managing and utilizing these resources, which will inform strategies to strengthen such empowerment. The S-O-A-R (Strengths, Opportunities, Aspirations, Results) approach has been employed to enhance qualitative analysis across three operational areas of KPH Kulawi. Findings indicate that community capacity to manage forest areas is bolstered by elements of local wisdom. This approach is recognized as an effective strategy for safeguarding forest areas while simultaneously improving the community's economic well-being.